DIRECTION OF MENTALLY DISABLED STUDENTS TO PROFESSIONS - Usmanova Mukhlisakhan Sobirovna; Khakimjonova, daughter of Nozanin Alijon (Journals Park Publishing, 2024)
In this article, the importance of vocational orientation of mentally retarded students in technology classes, and the knowledge and skills they develop in them is highlighted.
Keywords: mentally retarded, profession, inclusive education, corrective, correctional educator, demonstrativeness.